PEMANFAATAN LAYANAN PERPUSTAKAAN KELILING OLEH DINAS PERPUSTAKAAN DAN KEARSIPAN PROVINSI NUSA TENGGARA BARAT (NTB) - Bq. Laela Uswatun Hasanah; I Putu Suhartika; I Ketut Gede Harsana (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2025)
One service that the Library and Archives Service of West Nusa Tenggara Province offers is mobile library services. These help make reading and information sources more accessible to the public, particularly in places that don't have permanent library services. People, particularly those living in rural or otherwise inaccessible locations, now have easier access to the information resources they need thanks to mobile library services. Interviews and participant observation of librarians and patrons serve as the data gathering tools for this qualitative research. The study's findings show that the community has made good use of the mobile library services. The presence of mobile library services has a positive impact, and this service increases the community's interest in reading. The service provides adequate facilities and a varied collection of books, and it also presents various supporting activities. The service is open to various groups without limiting age. Research conducted in the West Nusa Tenggara Province demonstrates the significant significance that mobile library services have in promoting literacy among the local population.